Objective Foundations of Ethics and Prospects for Its Development: Information and Communication Approach - Gabrielyan, Oleg; Suleimenov, Ibragim (Conatus - Journal of Philosophy, 2025)
The paper considers the objective foundations of ethics as a system providing self-regulation of society. An information and communication approach to the study of the laws of the formation of ethical norms and the interpretation of ethics as a specific transpersonal information structure is proposed. It is shown that the ethical system can be analyzed on the basis of a neural network model of society, which proves the possibility of the emergence of transpersonal information objects of various types, including those responsible for the functioning of ethics. Moreover, the thesis is put forward and substantiated that human evolution will take place in the direction of the formation of ethics as a third signaling system. There are no other regulators of socio-natural human behavior. In this direction, humanity will need to reach the level of macrocivilizational subjects and later to the level of self-identification as a human civilization with a single ethical system or coordinated at the level of intercivilizational integration.